1995
DOI: 10.1017/s0031182000077027
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium yoelii nigeriensis: the effect of high and low intensity of infection upon the egg production and bloodmeal size of Anopheles stephensi during three gonotrophic cycles

Abstract: Anopheles stephensi mosquitoes showed a reduction in fecundity over 3 successive gonotrophic cycles, after becoming infected with Plasmodium yoelii nigeriensis. This effect could be observed at high oocyst burdens (> 75) or at low oocyst burdens (mean of 4.36). Mean bloodmeal size of the infected mosquitoes was significantly reduced only when feeding upon a mouse with a high gametocytaemia and the conversion of the bloodmeal into eggs by the infected mosquitoes was disrupted. Patterns of infected mosquito mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 23 publications
3
61
0
1
Order By: Relevance
“…The energetic costs of defense are difficult to measure and are generally inferred by making comparisons between fitness traits of susceptible or resistant hosts (Ferdig et al 1993;Yan et al 1997;Webster and Woolhouse 1999). Despite these studies, we have little understanding of what aspects of the immune system are costly and exactly where the costs are imposed.There is persuasive evidence from laboratory and field studies that malaria-infected mosquitoes are less fit than uninfected ones, with both longevity and reproductive success affected (Lyimo and Koella 1992;Hogg and Hurd 1995;Ahmed et al 1999;Anderson et al 2000). Despite the selection pressure that these fitness costs will impose, totally refractory A. gambiae mosquitoes are rarely reported in the field (Haji et al 1996;Schwartz and Koella 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The energetic costs of defense are difficult to measure and are generally inferred by making comparisons between fitness traits of susceptible or resistant hosts (Ferdig et al 1993;Yan et al 1997;Webster and Woolhouse 1999). Despite these studies, we have little understanding of what aspects of the immune system are costly and exactly where the costs are imposed.There is persuasive evidence from laboratory and field studies that malaria-infected mosquitoes are less fit than uninfected ones, with both longevity and reproductive success affected (Lyimo and Koella 1992;Hogg and Hurd 1995;Ahmed et al 1999;Anderson et al 2000). Despite the selection pressure that these fitness costs will impose, totally refractory A. gambiae mosquitoes are rarely reported in the field (Haji et al 1996;Schwartz and Koella 2002).…”
mentioning
confidence: 99%
“…There is persuasive evidence from laboratory and field studies that malaria-infected mosquitoes are less fit than uninfected ones, with both longevity and reproductive success affected (Lyimo and Koella 1992;Hogg and Hurd 1995;Ahmed et al 1999;Anderson et al 2000). Despite the selection pressure that these fitness costs will impose, totally refractory A. gambiae mosquitoes are rarely reported in the field (Haji et al 1996;Schwartz and Koella 2002).…”
mentioning
confidence: 99%
“…Second, the two groups developed their ovaries to comparable extents: if anything, the females exhibiting high oocyst numbers were more likely to have developed only a few eggs (0-4), an observation consistent with those of Hogg and Hurd. [33][34][35] The Dox-A2 4.3 homozygotes were recovered in less than the expected 50% of backcross females at both low and high infection levels. Because the contingency 2 suggested that the deficit was independent of infection level, this should not be a consequence of parasitism per se, unless even a very low level of infection is selectively toxic.…”
Section: Discussionmentioning
confidence: 88%
“…Mutation of a gene contributing to what is normally a tightly controlled and highly localized phenol oxidase activation may result in enhanced ease of activation. This could have been selected for in nature because even low oocyst burdens are detrimental to the fecundity of female mosquitoes, [33][34][35] possibly even more detrimental than the toxicity of highly reactive products of catecholamine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Plasmodium oocysts in the midgut has been correlated with reduced mosquito fecundity in laboratory and natural systems (Hogg and Hurd 1995a, 1995b, 1997. Decreased fecundity was also associated with alterations in utilization of the yolk protein vitellogenin by ovaries in infected versus uninfected mosquitoes .…”
Section: Fitness Costs and Evolution Of Malaria Resistancementioning
confidence: 99%